PERAN SEJARAH DALAM PEMBENTUKAN KARAKTER DAN IDENTITAS BANGSA - Aliyah, Siti; Pranoto, Reno Ardi; Agustin, Erin Rosna; Trisetiyoko, Didik (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
History learning plays an important role in shaping students' national character by strengthening their understanding of the nation's history, noble values, and collective awareness as a nation. Through an educational, inspiring, recreational, and instructive approach, history allows students to understand past events in depth, take inspiration from national figures, and develop critical thinking skills. The educational function teaches moral values ​​and wisdom, the inspirational function provides motivation from national figures, the recreational function makes learning more interesting, and the instructive function strengthens students' critical analysis skills. In addition to transferring knowledge, history learning also forms temporal awareness, where students are invited to understand the long-term consequences of past events. This understanding fosters an attitude of love for the homeland and a commitment to contributing to national development, as well as respecting ethnic, cultural, and religious diversity in national life. Thus, history learning makes a significant contribution to building a strong national identity, multicultural awareness, and critical thinking skills that are essential for students in facing challenges in the modern era.